MODEL PEMBELAJARAN COLLABORATIVE CREATIVITY (CC) BERBANTUAN VIRTUAL LABORATORY PADA PEMBELAJARAN FISIKA DI SMA - Dian Pratiwi; Sri Astutik; Maryani Maryani (FKIP Universitas Jember, 2018)
Collaborative Creativitiy (CC) intructional model is instructional model to training student’s physics concept and scientific process skill with apply CC which describe procedures systematically and used to guide teachers to help students how to identify problems, exploring creative ideas, collaborative creativity, elaboration, and evaluation of physics concept and scientific process skill. The implementation of the instructional model will be more effectively done by utilizing the media realized in computer tecnology. The type of this research was an experimental research by post-test control group design. Population of the research was all student’s at SMAN 1 Pakusari. The technique to collect data was documentation, observation, interview, and tests.The results of this research were the averaage of student’s science process skills was 90,04% (good criteria) and the significant difference on the physics concept of student was 0,002 using T-Test SPSS 23. This reseacrh can be concluded: first, the average of student’s science process skills is in good criteria. Secondly, threre is a significant difference in concept governance of students who use Collaborative Creativitiy with Virtual Laboratory and who do not use Collaborative Creativitiy with Virtual Laboratory.Key word: Collaborative Creativity, Physics Concept, and Scientific Process Skill.